Studi Naskah Batak: Masalah dan Prosedurnya - Giuseppina Monaco (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2017)
This paper will provide an overview about the study of the Batak manuscript. The first objective of this paper is to underline the importance of giving new impetus to the study of manuscripts, which is a large part of the culture of the one country. This paper will also provide an overview of the materials and procedures used to make the pustaha, the language used, and the contents of one manuscript that the author has worked on for her MA thesis. The purpose of this paper is also to illustrate the difficulties encountered in attempting to study the Batak script and to propose a description of the specific language used in pustaha, the Poda language. The material in this paper is expected to incite awareness to all of us in keeping the ancient texts in order to preserve their wholeness and authenticity. The texts are indeed the fragile part of one culture. That is why the old texts are very valuable to us: they survived the destruction of time, and now they contain and reflect an ancient culture, which no longer exists, but this ancient culture is tied directly with the ancestors and it is a part of the national cultural heritage. —– Makalah ini akan memberikan gambaran tentang studi naskah Batak. Tujuan pertama dari makalah ini adalah menekankan pentingnya memberikan dorongan baru pada studi naskah Batak, yang merupakan satu dari sebagian banyak dari kebudayaan Nusantara ini. Lalu, makalah ini akan memberikan gambaran tentang materi dan prosedur yang digunakan untuk membuat pustaha, tentang bahasa yang digunakan, dan tentang isi dari salah satu naskah yang sudah penulis kerjakan untuk tesis. Selain itu, makalah ini akan juga memberikan gambaran tentang kesulitan yang dihadapi dalam upaya untuk belajar naskah Batak dan mengusulkan deskripsi bahasa khusus yang digunakan dalam pustaha, yaitu bahasa Poda. Materi dalam makalah ini hendaknya menumbuhkan kesadaran kepada kita semua untuk menjaga naskah-naskah kuno agar tetap terjaga keutuhan dan keasliannya. Naskah-naskah memang hal yang rapuh. Itulah sebabnya naskah-naskah yang tua sangat berharga bagi kita: mereka selamat dari kerusakan waktu, dan sekarang mereka mengandung dan mencermikan sebuah budaya yang kuno, yang memang tidak ada lagi.